2019
DOI: 10.1177/0008417419832327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of task complexity on handwriting kinetics

Abstract: Background. Knowledge regarding the relationship between writing kinetics and the difference among writing tasks is limited. Purpose. This study examined the differences in handwriting performance when doing tasks with different levels of challenge from both temporal and kinetic perspectives among children in four different age groups. Method. The cross-sectional design introduced a force-acquisition pen to detect differences of pen grip and writing kinetics among 170 school-age children doing writing tasks at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Shim et al [23] also proposed a system measuring contact forces from three digits. However, a limited number of studies have reported children's handwriting performance by investigating the forces directly applied from the digits [13,15,18,20,[24][25][26]. As studies on digit force are still limited, this study was designed as an observational study to provide insights into the issue.…”
Section: Plos Onementioning
confidence: 99%
“…Shim et al [23] also proposed a system measuring contact forces from three digits. However, a limited number of studies have reported children's handwriting performance by investigating the forces directly applied from the digits [13,15,18,20,[24][25][26]. As studies on digit force are still limited, this study was designed as an observational study to provide insights into the issue.…”
Section: Plos Onementioning
confidence: 99%
“…Recent analyses of the cytoarchitecture and connectivity of neural areas have provided four key regions that appear to be important in categorizing the brain's writing system [57,[71][72][73]. i) The fusiform gyrus is most relevant to selectivity to letter, word stimuli and deriving "word-form" [74][75][76][77][78].…”
Section: The Neural Correlates Of Handwritingmentioning
confidence: 99%
“…It is based on registration of tremor data using TTM with active movement of the hand. Past research is mostly limited to measuring "average" forces or is related to pathological tremor (Baur, Fürholzer, Jasper, Marquardt, & Hermsdörfer 2009;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%